What Is Physical Activity? A Holistic Definition for Teachers, Researchers and Policy Makers - Piggin, Joe (Frontiers in sports and active living, 2020)
This conceptual analysis presents an argument that a new and broader definition of physical activity is needed for educators, researchers, and policy makers. To build a case for change, this paper has four parts. First, it outlines why definitions are important. Second, the current dominant definition of physical activity is examined and critiqued. Third, the case for change to the dominant definition is made. Fourth, a new, broader definition for physical activity is offered and justified. The new, broader definition of physical activity is proposed as involving "people moving, acting and performing within culturally specific spaces and contexts, and influenced by a unique array of interests, emotions, ideas, instructions and relationships."